Olivia - Garvice, Charles, 1850-1920 (Salt Lake City, UT : Project Gutenberg, 2023)
"Olivia: or, It was for her sake" by Charles Garvice is a romantic novel written in the late 19th century. The book introduces the charming young Olivia Vanley, who finds herself entangled in a web of mystery and intrigue involving a new neighbor, Mr. Faradeane, who has mysteriously purchased a local property. As the story unfolds, themes of love, societal expectations, and personal secrets begin to emerge. At the start of the novel, we are introduced to a picturesque village in Devonshire where Olivia lives with her family. During a tea gathering with an old solicitor, Mr. Sparrow, and her aunt, Miss Amelia Vanley, they discuss the strange behavior of Mr. Faradeane, who has taken up residence at The Dell$1 (Ba cottage he recently bought under mysterious circumstances. Olivia's curiosity is piqued as the conversation reveals that Faradeane prohibits female visitors and maintains a reclusive lifestyle, raising speculations among the guests. Amidst this chatter, Olivia's thoughts drift towards her feelings for Lord Granville, a young man with whom she shares a deeper connection. The blend of romance and the enigma surrounding Mr. Faradeane sets the stage for the unfolding drama and relationships within the story. (This is an automatically generated summary.)s
Release date is 2023-04-02
David Edwards, Krista Zaleski and the Online Distributed Proofreading Team at https://www.pgdp.net (Images courtesy of the Digital Library@Villanova University.)
Keywords: English fiction; Dime novels